Radical hysterectomy after chemoradiation in FIGO stage III cervical cancer patients versus chemoradiation and brachytherapy: Complications and 3-years survival. Issue 10 (October 2016) - Fanfani, F.; Vizza, E.; Landoni, F.; de Iaco, P.; Ferrandina, G.; Corrado, G.; Gallotta, V.; Gambacorta, M.A.; Fagotti, A.; Monterossi, G.; Perrone, A.M.; Lazzari, R.; et al.
Abstract: Background: To compare patterns and rates of early and late complications, and survival outcome in FIGO stage III cervical cancer patients underwent to radical hysterectomy after chemo-radiation (CT-RT) vs. chemo-radiation alone. Methods: Between May 1996 and April 2013 150 FIGO stage III cervical cancer patients were treated. We divide patients according to type of treatment: 77 were submitted to standard treatment (Group A), and 73 to completion hysterectomy after chemo-radiation (Group B). Results: The baseline characteristics of the 2 groups were superimposable. We observed lower intra-operative and treatment-related early urinary and gastro-intestinal complications in Group B with respect to Group A (p < 0.001). Vascular complications were registered only in Group B (p < 0.001). We found a significantly higher rate of local recurrences in the Group A than in the Group B (p < 0.002). We registered 29 deaths in the Group A and 22 in the Group B (p = 0.021). The 3-years disease-free survival rate in the Group A and in the Group B was 62.9% and 68.3%, respectively (p = 0.686), and the 3-years overall survival rate in the Group A and in the Group B was 63.2% and 67.7%, respectively (p = 0.675). Conclusions: This study confirms that radical hysterectomy after CT-RT is an effective therapeutic approach for advanced cervical cancer. Further prospective and randomized studies should be performed in order to solve the question about the standard approach, and how the different pattern of complication could impact on the quality of life.